m+3-5=5m+3m+7

Simple and best practice solution for m+3-5=5m+3m+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m+3-5=5m+3m+7 equation:


Simplifying
m + 3 + -5 = 5m + 3m + 7

Reorder the terms:
3 + -5 + m = 5m + 3m + 7

Combine like terms: 3 + -5 = -2
-2 + m = 5m + 3m + 7

Reorder the terms:
-2 + m = 7 + 5m + 3m

Combine like terms: 5m + 3m = 8m
-2 + m = 7 + 8m

Solving
-2 + m = 7 + 8m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-8m' to each side of the equation.
-2 + m + -8m = 7 + 8m + -8m

Combine like terms: m + -8m = -7m
-2 + -7m = 7 + 8m + -8m

Combine like terms: 8m + -8m = 0
-2 + -7m = 7 + 0
-2 + -7m = 7

Add '2' to each side of the equation.
-2 + 2 + -7m = 7 + 2

Combine like terms: -2 + 2 = 0
0 + -7m = 7 + 2
-7m = 7 + 2

Combine like terms: 7 + 2 = 9
-7m = 9

Divide each side by '-7'.
m = -1.285714286

Simplifying
m = -1.285714286

See similar equations:

| 5a-3-5a=-6-6a+5a | | (x-6)(x-2)=0 | | 2/7+5/7=-1/7 | | 2(p-14)=8 | | -x+3=30 | | 16-16x+3x^2=0 | | x-4=-10+4x | | 2(t-9)+-18=-4 | | -12+1.5y-6y=18 | | m+3-5=-5m+3m+7 | | 8x-4=8x-20 | | 4r+48/16=2r-18/2 | | 5/244/24 | | 18(n)=7.2 | | 24.50t+9.50=c | | 3-6(2v+3)=-111 | | 5.27=0.02036x(1-0.02036) | | 4x-36-24x=2-(6+4x) | | 4(x+3)+44=-4x | | -9+(5x)=6x-4 | | -3x-6-9x=7 | | -8+x+x=10 | | 7(2-5y)+10y=89 | | Ax-9=12 | | 5.27=0.0509x(1-0.0509) | | -9(5x)=6x-4 | | 2x-5(x-2)=-8+3x-6 | | 12x-30=4x+2 | | 15x^2+x-7/3x+2 | | x/2-1.25=5 | | x-4/4-1=x-10/5 | | 5x+26=21+4x |

Equations solver categories